GRAFT STABILITY AFTER ENDOTHELIAL KERATOPLASTY - Jovanovic, Vesna (Vojnosanitetski pregled, 2015)
Aim: To establish the graft stability after Descemet stripping with endothelial keratoplasty (DSEK), compare it to the graft stability after endothelial keratoplasty (EK) with the intact posterior corneal layers in the rabbit cornea, and to investigate the nature of wound healing. Methods: Adult white rabbits were used( N=20), divided in two experimental groups. Ten rabbits underwent monocular DSEK, and ten, EK without Descemet stripping. On the second postoperative day Lindstrom roller was used to try to dislocate graft horizontally in each animal, and corneas were processed for the light microscopy study. Results: Rolling the Lindstrom instrument over the corneal surface did not cause horizontal dislocation in any of the operated eyes. In the DSEK group light microscopy revealed the lack of inflammation and fibrosis at the donor – recipient interface (DRI), but was distinctive on histology. Retrocorneal membrane was found in two eyes. In the group with EK only, the host Descemet`s membrane (DM) was intact without endothelial cells, with good graft apposition, without inflammation or fibrosis, and there was no retrocorneal membrane. Conclusion: This study suggests that there is no difference in graft stability in DSEK compared to EK without DM stripping in rabbit corneas. The wound healed at DRI by hypocellular scarring only, in both experimental groups.